ASHRAE laboratory design guide : planning and operation of laboratory HVAC systems. (ASHRAE, 2015)
"Reference manual for planning, design, and operation of laboratory HVAC systems to reduce the laboratory's energy footprint while ensuring safety, providing good comfort and indoor air quality, and protecting the integrity of experiments; includes online access to electronic design tools that illustrate features of laboratories and provide practical design aids."
Revised edition of: ASHRAE laboratory design guide / Ian B.D. McIntosh, Chad B. Dorgan, Charles E. Dorgan. 2001.
Keywords: Laboratories -- Design and construction.; Laboratories -- Safety measures.; Laboratories -- Energy conservation.; Buildings -- Environmental engineering.; elektronické knihy; electronic books